Content Validity and Readability Evaluation of the Waek AI-Based Game Application for Bullying Prevention and Mental Health Promotion Among Generation Z - Miftakhul Ulfa; Ari Dwi Sulaksono; Ahmad Guntur Alfianto; Mizam Ari Kurniyanti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Generation Z faces increasing mental health challenges, often worsened by bullying and cyberbullying. Digital-based interventions need to be both engaging and understandable for this demographic. This study aimed to evaluate the content validity and readability of the Waek AI-based game application designed for bullying prevention and mental health promotion among Generation Z youth. A descriptive quantitative design was employed with six expert validators, consisting of three psychiatric nursing lecturers and three IT professionals. Data were collected using structured validation sheets and analyzed using the Aiken’s V coefficient for content validity and the Indonesian Digital Readability Index (IDRI) for readability.The application achieved an Aiken’s V score of 0.947, indicating excellent content validity, and an IDRI score categorized as moderate-to-easy (71–80), demonstrating high readability. The Waek AI-based game application possesses strong content validity and readability, supporting its feasibility as a digital tool for bullying prevention and mental health promotion among Generation Z.